PEMENUHAN HAK ANAK DALAM LEMBAGA PEMBINAAN KHUSUS ANAK (Studi Kasus Pada Lembaga Pembinaan Khusus Anak Kelas II A Kota Pekanbaru tahun 2024) - Pandi Saputra; Fakhri Usmita (UIR PRESS, 2025)
This study aims to analyze the fulfillment of the rights of children in conflict with the law at the Class II Special Child Development Institution (LPKA) in Pekanbaru. The research employs a qualitative method with a descriptive approach, using data collection techniques such as interviews, observation, and documentation studies. The findings indicate that, in general, the fulfillment of children’s rights at LPKA Class II Pekanbaru has been implemented relatively well, particularly in aspects of protection, guidance, and supervision by officers. However, obstacles remain in the fulfillment of children’s rights in the field of education, especially regarding limited access to information and supporting facilities for the learning process. Therefore, improvements in facilities and more optimal policies are required to ensure the comprehensive fulfillment of the rights of children in conflict with the law in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.